Relationship between homocysteinaemia and sympathetic skin response in Parkinson's disease - Crespo-Burillo, J A; Almarcegui-Lafita, C; Dolz-Zaera, I; Alarcia-Alejos, R; Roche, J C; Ara, J R; Capablo-Liesa, J L (Revista de neurologiá, 2017)
High levels of homocysteine linked to treatment with levodopa have been observed in patients with Parkinsons disease (PD). Our aim was to assess the influence of serum homocysteine levels and other PD-related on the sympathetic skin response. An observational, cross-sectional study was conducted that consecutively included patients with PD. We unilaterally assessed the sympathetic skin response in the upper limbs. We measured the influence of PD severity (measured by the Hoehn and Yahr and the Schwab and England scales, and the Unified Parkinson Disease Rating Scale) and blood homocysteine, vitamin B12 and folic acid levels on the latency and amplitude of the sympathetic skin response. A total of 78 patients were enrolled, and all achieved a sympathetic skin response. In the bivariate analysis, latency was significantly correlated with age, age at PD onset and homocysteinaemia levels. The presence of hyper-homocysteinemia was associated with a longer latency. The amplitude was only correlated with the score on the Schwab and England scale. In the multivariate analysis, age was the only variable that showed a significant association with the latency duration and homocysteine levels. A direct association could not be established between the increase in homocysteinaemia levels and sympathetic skin response dysfunction in PD. The results of the multivariate analysis suggest that latency prolongation in elderly patients could be due to the fact that these patients have higher blood levels of homocysteinaemia.